Sistem Informasi Administrasi Kependudukan Pada Kantor Desa Siau Dalam Kabupaten Tanjung Jabung Timur - Riska, Riska; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2022)
The problem faced in the activity residents data processing at the office of Siau Dalam village is that storage media is unreliable so that it is in file search and not in time in the provision of reports. The lack of verifying data accuracy is likely to be incorrect in recording and monitoring the service of the archivist population. As for the purpose of this research to assist the Siau Dalam village its specialized administration of the public service. Researchers are analyzing data collection by observing current systems as well as interviews with administrative and village leaders to help with the data collection. The analysis and design of the system uses linear modeling language approaches using UML (unified modeling language) and Balsamiq mockups with the end results of the information system’s prototype. The design of this system of occupation administration will enhance the performance of government lov in population data management, and publish citizen papers, as well as the ease in making the report of occupation at the village village of Siau Dalam Kabupaten Tanjung Jabung Timur That can be served quickly, precisely, and accurately.